Rooftop PV with battery storage for constant output power production - Jabal Ameli, Nasim (Curtin University, 2013)
In this thesis, the application and control of battery storage (BS) system is introduced and developed to compensate for output power changes of rooftop PVs due to variations in the environmental conditions and household loads. A practical battery storage energy management strategy (BS-EMS) for operating small scale grid-connected rooftop PVs is implemented such that the net delivered output power to the grid is constant under various operating conditions.